Valco San Paolo Student Housing in Rome - 2007-2013 Architectural design 2018-2021 Construction completion. - Dall'Olio, Lorenzo; Mancini, Francesco; Ciambrelli, Nicoletta; Gori, Viviana; iacovone, Maria (ANCE Servizi srl | Edilstampa, 2022)
The dimensions of the site, urban planning restrictions and the density of the building programme determined the volume of the building: a single, imposing linear sign, 240 metres long and three storeys above ground, with a depth of 17 metres. A horizontal condition was immediately dominant and inevitable. The horizontal reading of the exteriors is counterbalanced inside by a vertical dimension, evoked in numerous double and triple height spaces of the main atrium and classrooms. Different sized living rooms, study rooms, kitchens, libraries, games rooms, meeting rooms, classrooms, a gym on one side, bedrooms, almost all single, on the other side, though grouped together in shared nuclei. A residence for 200 students inherently suggests a repetitive composition that the project sought to temper by introducing diverse typological variations and a series of collective spaces, exceptional functions, loggias and terraces that interrupt the serial nature of the module of rooms and its relative system of windows.